Fabrication of Contour Cavity Using Multi-Exposure Lithography for MEMS Capacitive Microphone - Jantawong, Jirawat; Atthi, Nithi; Leepattarapongpan, Chana; Jeamsaksiri, Wutthinan; Austin, Anu; Sooriakumar, Kathirgamasundaram; Niemcharoen, Surasak (My University, 2018)
This paper presents a novel technique to optimize a capacitive pressure sensor with multi-exposure dose lithography. As part of achieving high signal to noise ratio (SNR) in microphone, a new design was implemented. The new design defies the conventional wisdom of parallel plate theory and implement a concept of contour cavity (backplate) to follows the diaphragm deflection. This 3-dimensional contour cavity (CC) is fabricated by multi-exposure dose lithography with single silicon etching process. The CC structure with different etched depth of 0.65, 1.15, and 1.57 micron were fabricated by multi-exposure dose of 92, 120, and 210 mJ/cm2on 5.0 micron thick photoresist and single step etching with CF4/O2plasma (Si/PR etch selectivity: 1.3). Due to this novel contour cavity design, polysilicon membrane with 0.8 micron thick and a diameter of 930 micron structure produces the capacitance value of 2.88 pF, which is 28.6% higher than that of conventional parallel plate capacitive sensor.
Keywords: 3-D lithography; Box cavity; Contour cavity; Membrane; MEMS capacitive microphone; Multi-exposure; Silicon microphone